2022
DOI: 10.1158/1078-0432.ccr-21-4504
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Chemotherapies Retain Antitumor Activity in Desmoid Tumors Independent of Specific Mutations inCTNNB1orAPC: A Multi-institutional Retrospective Study

Abstract: Purpose: Determine whether specific CTNNB1 or APC mutations in patients with desmoid tumor were associated with differences in clinical responses to systemic treatments.Experimental Design: We established a multi-institutional dataset of previously treated patients with desmoid tumor across four U.S. sarcoma centers, including demographic and clinicopathologic characteristics, treatment regimens, and clinical and radiographic responses. CTNNB1 or APC mutation status was determined from prior pathology records,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…Hence, it is possible to diagnose sporadic BDF with no evidence of CTNNB1 mutation ( 8 ). Finally, identifying mutations might be helpful in case of diagnostic doubt but mutation status does not predict systemic therapy responses ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is possible to diagnose sporadic BDF with no evidence of CTNNB1 mutation ( 8 ). Finally, identifying mutations might be helpful in case of diagnostic doubt but mutation status does not predict systemic therapy responses ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“… 17 Contrarily, drug treatment with considerable side effects, including anticancer drugs and molecular targeted drugs, has been reported to control DF with any type of CTNNB1 mutation. 35 , 36 Altogether, DF that cannot be controlled by AS can be suppressed by anticancer drugs or molecular target drugs even if it is S45F. Tumor diameter, gender, recurrent cases, limb location, and juvenile development have been reported as risk factors for recurrence regarding surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The CTNNB1 S45F mutation has been previously reported as a risk factor for recurrence after surgical treatment 5,32–34 and associated with tumor progression in patients with oral COX‐2 inhibitor treatment 17 . Contrarily, drug treatment with considerable side effects, including anticancer drugs and molecular targeted drugs, has been reported to control DF with any type of CTNNB1 mutation 35,36 . Altogether, DF that cannot be controlled by AS can be suppressed by anticancer drugs or molecular target drugs even if it is S45F.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, most studies have suggested that DTF with a p.S45F mutation is more clinically aggressive. A recent large retrospective multi-institutional study found no significant impact of mutation subtype on the efficacy of chemotherapy or tyrosine kinase inhibitors, although there was a trend toward worse outcomes with an APC mutation [ 26 ].…”
Section: Discussionunclassified